The Sensory Deprivation Tank – A Time Machine - Phillips, Matthew T (Anthropology of consciousness, 2022)
This paper explores Henri Bergson’s understanding of time in relation to the experience of the sensory deprivation tank. In this exploration, the tank is presented as a time machine: a machine that separates time from space and takes the floater into an experience of what Bergson describes as pure time. At the same time, the tank acts as a kind of phenomenological epoché that, through the disabling of the floater’s sensory-motor schema, literally suspends the human being outside of the world and forces them to reconsider their previous judgements and understandings of consciousness and time. The tank is tied in with contemporary scientific and philosophical discourses on consciousness, such as those of David Chalmers and what he has described as the hard problem of consciousness. As Chalmers discusses, the hard problem requires a radically new type of thinking beyond contemporary science and its inherent materialistic and mechanistic worldview. The tank is presented as a machine that could play a part in this radical rethinking of consciousness—a literal black box working through the black box problems of consciousness.